Biodegradable films based on chitosan, xanthan gum, and fish protein hydrolysate. Issue 23 (13th February 2017) - de Morais Lima, Maria; Bianchini, Daniela; Guerra Dias, Alvaro; da Rosa Zavareze, Elessandra; Prentice, Carlos; da Silveira Moreira, Angelita
ABSTRACT: The aim of this study was to develop films based on chitosan, xanthan gum, and protein hydrolysate of Whitemouth croaker ( Micropogonias furnieri ), evaluating their antioxidant activity and also their mechanical, physical, structural, morphological, thermal, and barrier properties. The mixture of xanthan gum and protein hydrolysate promoted some changes in chitosan films. The addition of xanthan gum increased tensile strength and changed the color parameters of films. The addition of Whitemouth croaker protein hydrolysate increased the antioxidant activity of the films. However, higher concentrations of hydrolysate tend to increase moisture and decrease their tensile strength. All films had homogeneous structure, with no phase separation and fissures. Significant differences in water solubility and water vapor permeability were not observed by the addition of xanthan gum and protein hydrolysate. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44899. Abstract :